Efektivitas Program Beasiswa untuk Meningkatkan Prestasi Mahasiswa (Kasus pada Mahasiswa Penerima Beasiswa Beastudi Etos di Jabodetabek - Mardiyanti Mardiyanti; Ninuk Purnaningsih; Prabowo Tjitropranoto (Jurnal Penyuluhan, 2014)
For achieve educational equity, government, private and non government organization provide scholarships. Scholarships are awarded as an effort to empower the recipients. Therefore this study aims to (1) analyze the scholarship program based on the concept of empowerment, (2) measure the factors that influence academic achievement of grantees. This research was conducted to 41 grantees Beastudi Etos at Jabodetabek during November-December 2013. The results showed that the scholarship is effective to be an empowerment program. Because it increase achievement motivation of grantees, and create positif environment to support learning process.Keywords: academic achievement, effectiveness of scholarship